Pertanggungjawaban Korporasi terhadap Pencemaran Lingkungan Hidup : Studi Pada Pt Horizon Bandar Bahru di Batam - Tantimin Tantimin (Journal of Judicial Review, 2017)
Development that affects the environment, such as pollution and / or damage to the environment, which has a wide and very dangerous impact on people's lives. Such as Buyat Bay Pollution Case, Lapindo Mud Case in Sidoarjo, Illegal Logging Case Adelin Lis in Medan, Case of Imported Waste from Australia, Mud Waste Import Case from Singapore for reclamation of Pelambung Bay and Nipah Island, and Case of Import of Hazardous and Toxic Waste (B3 ) from the "Leisure World" Shipper in Batam. The purpose of this paper is to find out how the system of corporate responsibility towards environmental pollution in the positive law of Indonesia and how the accountability of PT. Horizon Bandar Bahru against environmental pollution. The method in this writing is Normative Legal Writing Method. Data collection is done through library research by studying legal provisions on matters relating to corporate responsibility to environmental pollution. The data is then drawn and related analyzed descriptively-qualitative. Based on the results of the author's writing that the system of corporate responsibility in environmental pollution can take the form of criminal responsibility, civil liability and administrative accountability. This liability may be requested because the corporation currently in the form of a legal entity (Limited Liability Company / PT) in the business of utilizing the environment conducting business activities that may lead to pollution or / or damage to the environment. Therefore PT Horizon Bandar Bahru, corporation as a legal subject in pollution and / or environmental damage must be responsible.